Cardiovascular Magnetic Resonance in Acute ST-Segment–Elevation Myocardial Infarction: Recent Advances, Controversies, and Future Directions. Issue 18 (1st May 2018) - Bulluck, Heerajnarain; Dharmakumar, Rohan; Arai, Andrew E.; Berry, Colin; Hausenloy, Derek J.
Abstract : Although mortality after ST-segment elevation myocardial infarction (MI) is on the decline, the number of patients developing heart failure as a result of MI is on the rise. Apart from timely reperfusion by primary percutaneous coronary intervention, there is currently no established therapy for reducing MI size. Thus, new cardioprotective therapies are required to improve clinical outcomes after ST-segment–elevation MI. Cardiovascular magnetic resonance has emerged as an important imaging modality for assessing the efficacy of novel therapies for reducing MI size and preventing subsequent adverse left ventricular remodeling. The recent availability of multiparametric mapping cardiovascular magnetic resonance imaging has provided new insights into the pathophysiology underlying myocardial edema, microvascular obstruction, intramyocardial hemorrhage, and changes in the remote myocardial interstitial space after ST-segment–elevation MI. In this article, we provide an overview of the recent advances in cardiovascular magnetic resonance imaging in reperfused patients with ST-segment–elevation MI, discuss the controversies surrounding its use, and explore future applications of cardiovascular magnetic resonance in this setting.